The final score : six short novels [large type] - Winslow, Don, 1953- (William Morrow Large Print, 2025)
"In six all-new short novels written with trademark literary style, trenchant wit, and incisive characterization that have made Don Winslow 'America's greatest living crime writer' (The Providence Journal), this repeat New York Times bestselling author serves up a collection of tales sure to delight Winslow's most devoted fans and first-time readers" -- Back cover.